METHODOLOGY FOR DEVELOPING ESSENTIAL VOCABULARY FOR IELTS WRITING AND SPEAKING IN THE CONTEXT OF UZBEKISTAN - Shermatov Farrukh (Research Focus International Scientific Journal, 2025)
This thesis explores the essential vocabulary required for success in the IELTS Writing and Speaking sections. It highlights high-frequency academic terms, topic-specific vocabulary, and cohesive devices necessary for clear communication. Practical strategies for vocabulary acquisition and effective usage are also discussed to enhance candidates’ performance.